Respuesta :
Answer:
x =7
Step-by-step explanation:
Let's solve your equation step-by-step.
4 ( 2x − 3 ) = 6x + 2
Step 1: Simplify both sides of the equation.
4 ( 2x − 3 ) = 6x + 2
( 4 ) ( 2x ) + ( 4 ) ( −3 ) = 6x + 2 ( Distribute )
8x + −12 = 6x + 2
8x − 12 = 6x + 2
Step 2: Subtract 6x from both sides.
8x − 12 − 6x = 6x + 2 − 6x
2x − 12 = 2
Step 3: Add 12 to both sides.
2x − 12 + 12 = 2 + 12
2x = 14
Step 4: Divide both sides by 2.
2x / 2 = 14 / 2
x = 7
Hope it helps
Please mark me as the brainliest
Thank you